Model Design of Performance Improvement Strategy of Private Higher Education Using Analytic Hierarchy Process (AHP) Method and Mutivariate Data Analysis (MDA) - Sri Hartati; Kenny Puspita Sari; Satria Abadi (Komunitas Dosen Indonesia, 2018)
The development of the number of Private Universities in Indonesia requires Private Universities to have good Performance and Quality. Private Universities must apply a new angle of thinking that contains elements of flexibility, speed, innovation, and integration. Flexibility, speed, innovation and integration really need human resources full of creativity. Creativity can arise from human resources who have excellence in science. Thus, Private Universities is expected to not only be able to produce the best graduates, but also be able to develop two things contained in the Tri Dharma of higher education, namely researching the results of high-quality research and developing technology for community service. For that Private Universities must always be able to adapt, develop and make improvements through organizational learning. This study aims to determine the strategy model for improving performance using a combination of AHP (Analytical Hierarchy Process) and Multivariate Data Analysis (MDA) methods. The sample of this research is management that manages Private Universities (Private Universities leaders) from several Private Universities in the Province of Lamping. AHP (Analytical Hierarchy Process) method is an analytical tool that can be used to make decisions on conditions with complex factors, especially if the decision is subjective. While the Multivariate Data Analysis (MDA) method refers to the statistical technique used to analyze data that appears from more than one variable. The results of this study indicate that there is a significant effect. Organizational Learning Factors, External Environment, Reputation, Competence, Professionalism, and Performance have a significant effect on Private Private Universities Performance. These criteria and sub-criteria are used as references for Private Universities management as a strategy to improve Private Universities performance in Lampung Province. This is basically a model of reality where each decision involves more than one single variable. This research is important to determine the best model in Private Universities Performance Improvement strategies. The results of this study contributed to the decision maker or management of Private Universities as a reference material in the member policies in improving the Performance of Private Universities